(untitled) (Revista científica Olimpia, 2024)
It investigation has like intensity to design a brochure of small games that they make possible the fomentation of the interest related to games in the adults that they practice the musical aerobic gymnastics of living room in the sports combination July 26 the municipality Bayamo, province Granma. The study came true with 36 members of the group that are practicing of this mode, enmarcándose in the ages understood between 42 and 57 years, everything of the female sex. They used methods of the theoretic level, empiricist and statistician that allow verifying insufficiencies that limit the interest related to games in this group etario. A brochure of games to give solution to the presented problems is designed in mail with these results.